TREATMENT COMPLIANCE OF CHILDREN WITH EPILEPSY AT NGHE AN OBSTETRIC AND PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: Find out the status of adherence to treatment of children with epilepsy and severalfactors related to treatment at Nghe An Obstetrics and Pediatrics Hospital.Subjects-methods: Cross-sectional description all pediatric patients diagnosed with epilepsyaccording to WHO criteria and primary caregivers at Nghe An Obstetrics and Pediatrics Hospital.Result: There were 90 children who met the research criteria. 47.8% of children are in the 1-5age group, 91.1% of parents are direct carers. The education level of caregivers from high schoolor higher is 52.2%. The child's history had 24.4% of febrile convulsions. The duration of treatmentfor epilepsy lasted for the majority of patients over 2 years 52.2% and the majority of patientsreceived monotherapy with an antiepileptic drug 63.3%. The number of patients with goodadherence to treatment accounted for 44.4%. Finding a statistically significant relationshipbetween caregiver education and adherence (p < 0.05).Conclusions: The percentage of patients who complied with treatment and re-examination isnot high. Factor that was statistically significant for children's compliance is caregiver's educationlevel.
Keywords: Epilepsy, adherence to treatment.